The Long-Run Non-Neutrality of Monetary Policy: A General Statement in a Dynamic General Equilibrium Model. Issue 2 (3rd April 2019) - Kam, Eric; Smithin, John; Tabassum, Aqeela
ABSTRACT: This paper provides an explanation of the long-run non-neutrality of monetary policy in a dynamic general equilibrium (DGE) model with microfoundations. If the rate of time preference is endogenous there is no natural rate of interest. Therefore, if the central bank follows an interest rate rule this will affect the real rate of interest in financial markets and thereby the real economy. In principle, there is a negative relationship between the real rate of interest and the rate of inflation. This turns out to be nothing other than the historical forced savings effect, or the 20th century Mundell-Tobin effect.